(untitled) (Physical Education, Health and Social Sciences, 2026)
Late-night Instagram doomscrolling and compulsive consumption of short-form videos have become widespread among young adults, yet their mechanisms affecting sleep remain underexplored. This study examines whether perceived daily productivity loss mediates the relationship between doomscrolling and bedtime procrastination. A sample of 277 adults (ages 19–25) completed surveys assessing Instagram doomscrolling, perceived productivity loss, and bedtime procrastination. Results showed that higher doomscrolling frequency significantly predicted greater bedtime procrastination, with approximately 44% of this effect transmitted through perceived productivity loss. The findings suggest that the immediate gratification from short-form videos creates a subjective sense of wasted time, which paradoxically motivates individuals to stay awake longer in an attempt to compensate, forming a self-reinforcing cycle. The study extends Temporal Motivation Theory to digital media behaviours and sleep, highlighting that cognitive appraisal of time loss, not merely duration of use, drives bedtime delay. Implications for interventions targeting digital wellness and sleep hygiene are discussed, emphasizing strategies that address perceived productivity loss alongside self-regulation to reduce chronic sleep delay.